Da crise da dívida financeira à crise da dívida soberana: um debate sobre a Política Fiscal - Neris Júnior, Celso Pereira; Bertella, Mario Augusto [UNESP] (My University, 2013)
The financial crisis of 2007 brought the discussion of fiscal policy. This was used as a way for governments to mitigate the potential social and economic impacts of the crisis, since only the monetary policy would not be effective. Historically, banking crises engender increases in public debt, not only for the relief operations, but also by the policies of government primary spending and/or, as in the recent crises, by the purchase of the “toxic” financial assets. The discretionary fiscal policy is then discussed, since it is essential, it is required well articulated and coordinated actions in order to mitigate their respective current and future crisis.

A crise financeira de 2007 trouxe à tona a discussão sobre a política fiscal. Esta foi empregada como forma dos governos atenuar os impactos econômicos e sociais potenciais da crise, uma vez que apenas o expediente monetário não daria conta do processo. Historicamente, crises bancárias engendram aumentos das dívidas públicas, não somente pelas operações de socorro, mas também pelas políticas de gasto primário dos governos e/ou, como na crise recente, pela compra de ativos financeiros “tóxicos”. A discricionariedade da política fiscal é colocada em discussão, uma vez que, sendo ela imprescindível, requerem-se ações coordenadas e bem articuladas para que os países consigam mitigar suas respectivas crises atuais e futuras.